Efektifitas E-Learning Dengan Aplikasi Moodle pada Mata Kuliah Penelitian Pengembangan Program Studi Teknologi Pendidikan - Siti Muyaroah (Universitas Batanghari Jambi, 2019)
This research aims to determine the effectiveness of e-learning with Moodle at educational study program, baturaja university. This research is quantitative research with experimental method. Can be interpreted as the research methods used to find a specific treatment effect against the other in a state of control. This ressearch result in the effectiveness of e-learning for student learning outcomes on science subjects. Effectiveness is the success of an establishment of a system designed to engage students actively and independently in learning. T-test result there are effectiveness of e-learning.